2020
DOI: 10.3390/antiox9100920
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effects and Molecular Signaling of n-3 Fatty Acids on Oxidative Stress and Inflammation in Retinal Diseases

Abstract: Oxidative stress and inflammation play crucial roles in the development and progression of retinal diseases. Retinal damage by various etiologies can result in retinopathy of prematurity (ROP), diabetic retinopathy (DR), and age-related macular degeneration (AMD). n-3 fatty acids are essential fatty acids and are necessary for homeostasis. They are important retinal membrane components and are involved in energy storage. n-3 fatty acids also have antioxidant and anti-inflammatory properties, and their suppress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 234 publications
(257 reference statements)
1
18
0
Order By: Relevance
“…Specifically, docosahexaenoic acid (DHA; 22:6n-3), arachidonic acid (AA; 20:4n-6) and adrenic acid (22:4n-6) are the most abundant fatty acid in the retina [ 25 , 26 , 27 ]. Their physiological function include critical protective effects against different retinal diseases such as retinopathy of prematurity, age-related macular degeneration or DR [ 28 ]. For example, NPD1, a docosatriene derivative from docosahexaenoic acid, protects retinal epithelial cells from oxidative stress thanks to its anti-apoptotic effects [ 29 ], or their metabolism alteration by peroxisome dysfunction induces retinal defects [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, docosahexaenoic acid (DHA; 22:6n-3), arachidonic acid (AA; 20:4n-6) and adrenic acid (22:4n-6) are the most abundant fatty acid in the retina [ 25 , 26 , 27 ]. Their physiological function include critical protective effects against different retinal diseases such as retinopathy of prematurity, age-related macular degeneration or DR [ 28 ]. For example, NPD1, a docosatriene derivative from docosahexaenoic acid, protects retinal epithelial cells from oxidative stress thanks to its anti-apoptotic effects [ 29 ], or their metabolism alteration by peroxisome dysfunction induces retinal defects [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Hyperglycemia triggers various pathological alterations such as oxidative stress, inflammation, angiogenesis, increase of apoptosis of endothelial cells and neurons, and injury to the retinal blood capillaries [ 67 ]. Thus, with the previously described effects of omega-3 fatty acids, including α-linolenic acid (anti-inflammatory, anti-oxidative or anti-angiogenic proprieties among others) on such disorders, they are of immense interest in preventing DR [ 68 ].…”
Section: Polyunsaturated Fatty Acids and Human Healthmentioning
confidence: 99%
“…This high metabolism makes the retina especially vulnerable to oxidative stress damage. Numerous studies have shown that ROS contributes to vascular endothelial dysfunction and retinal neural degeneration [ 24 ]. Moreover, inflammation in the retina and neuron degeneration has been linked to excessive ROS formation, which can directly modify cellular molecules and impair their function.…”
Section: Protective Effects Of Dha Against Oxidative Stress In Eyementioning
confidence: 99%
“…n-3 PUFAs cannot be efficiently synthesized by the human body, so that adequate amounts depend on the consumption of foods rich in these compounds, such as fish and fish oil products ( Figure 3 ). DHA accounts for approximately 20% of the retinal weight and affects the development and survival of neurons and retinal vascular cells [ 24 ]. DHA is the dominant fatty acid of retinal phospholipids and plays a significant role in maintaining retinal integrity [ 25 ], also related to the increased production of GSH ( Figure 3 ).…”
Section: Protective Effects Of Dha Against Oxidative Stress In Eyementioning
confidence: 99%
See 1 more Smart Citation